Coprecipitation with nickel cycloheptanedionedioximate - Win, Sein Sein (My University, 1975)
The development of a new PFHS (precipitation from homogeneous solution) method for the determination of nickel is reported. Cycloheptane-dionedioxime was generated from 1,2-cycloheptanedione and hydroxylamine in solution in the presence of nickel ions to produce nickel cycloheptane-dionedioximate crystals. The reported method of synthesis of 1,2-cyclo-heptanedione was modified in order to obtain a pure product.
We product the results from kinetic studies on the nickel cycloheptane-dionedioximate precipitation reaction both in the absence and in the presence of two foreign ions, cobalt (II) and copper (II).
The developed PFHS method was useful in studies on the coprecipitation of cobalt and copper with nickel cycloheptanedionedioximate. Distribution diagrams were prepared using the two classical distribution laws for both systems studied. None of the limiting laws provided a satisfactory explanation of the observed data. Deviations observed in the behaviour of homogenous distribution coefficient and logarithmic distribution coefficient, D and λ, are interpreted in terms of kinetic parameters. The functional relationship between D and λ and the rate of nickel cycloheptanedionedioximate precipitation is reported.
A kinetic model, which relates the rate of precipitation per particle and the distribution coefficients was also tested in both co-precipitation systems. The model was found to be useful only to a limited extent.
Keywords: Chemistry; Chemistry